Global sourcing of knowledge services and innovation: a literature review - Swirski de Souza, Yeda; Gavronski, Iuri; Jacobus, Artur (Internext, 2015)
Global sourcing of knowledge services and innovation (GSKSI) has been subject of several studies in an array of areas, which include strategy and international management, economic geography, organizational behavior, operation management, among others. The objectives of this paper are twofold: a) to produce a summary of GSKSI studies and b) provide a research agenda for GSKSI. We conducted a systematic review of academic literature and found that, besides essays, reports and theoretical papers, the empirical studies on GSKSI can be distributed in four major categories: strategic and international management; technology and innovation management; labor, organizational behavior and human resources; and operations management. We also found that GSKSI analysis oscillate between an approach that connects this phenomenon to previous or existing practices, and another view that considers GSKSI a transformational phenomenon challenging extant theories and practices.